Effectively enhanced photocatalytic hydrogen production performance of novel noble metal-free Cu(OH)2/MoSe2-g-C3N4 ternary nanocomposite under visible light irradiation - Rameshbabu R.; Siaw Paw J.K.; Vinoth V.; Kumar R.S.; Kumar N.; Jadoun S.; Pugazhenthiran N.; Amalraj J. (Elsevier Ltd, 2025)
The present work presents a novel copper hydroxide-molybdenum diselenide-carbon nitride (3 % Cu(OH)2/MoSe2-g-C3N4, (3CM-CN)) ternary nanocomposite catalyst. This catalyst was synthesized using a three-step process: hydrothermal synthesis, ball milling, and wet impregnation. The focus of this research is on the hydrogen generation (H?) capabilities of this novel material. The catalyst was extensively characterized using various analytical techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), ultraviolet?visible (UV?Vis) spectroscopy, photoluminescence (PL) spectroscopy, and X-ray photoelectron spectroscopy (XPS), resulting in a comprehensive understanding of its structure, morphology, optical properties, and surface composition. The catalytic activity and mechanism of Cu(OH)2/MoSe2-g-C3N4 composites were investigated. The ternary nanocomposite catalyst significantly enhanced hydrogen production, achieving rates 7.7 times greater than g-C3N4 and 4 times greater than 3 % Cu(OH)2/MoSe2 (3CM). Its maximum production reached an impressive 3012 mol g?1 h?1. The analysis demonstrated a significant increase in active sites on the composite's surface, accompanied by an increase in the composite-specific surface area to 73 m2/g. The development of a ternary nanocomposite led to a higher rate of catalyst production for hydrogen generation while simultaneously decreasing the rate of electron-hole recombination. It gave an innovative strategy for constructing highly efficient composite catalysts for hydrogen generation very effectively. ? 2024 Elsevier Ltd